FINANCIAL MANAGEMENT ASSISTANCE FOR HADIPOLO KUDUS KNIFE CRAFTSMEN - Rochmad Winarso; Nita Andriyani Budiman; Budi Gunawan (International Journal of Engagement and Empowerment, 2021)
Hadipolo Village is one of the villages in Jekulo District, Kudus Regency which is a center for making tools made of iron, for example, knives. The knife-making business in Hadipolo Village has been developing for a long time and has been passed down for generations. Hadipolo knife is the product of Hadipolo Village which is well known in other areas and even in other provinces in Indonesia. One of the problems faced by Hadipolo knife craftsmen is the management of business finances. The purpose of this community service activity is to provide motivation and accounting knowledge to Hadipolo knife craftsmen to carry out financial management so that Hadipolo knife craftsmen can be more economically independent. The implementation method is divided into four stages, namely the lecture method, tutorial method, simulation method, and discussion method. The results achieved in this service activity are Hadipolo knife craftsmen gaining knowledge about simple financial management and the benefits of applying simple financial management to business progress